2005
DOI: 10.1002/eji.200526066
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of HMGB1 and RAGE for the maturation of human plasmacytoid dendritic cells

Abstract: Dendritic cells (DC) are key components of innate and adaptive immune responses. Plasmacytoid DC (PDC) are a specialized DC subset that produce high amounts of type I interferons in response to microbes. High mobility group box 1 protein (HMGB1) is an abundant nuclear protein, which acts as a potent pro-inflammatory factor when released extracellularly. We show that HMGB1 leaves the nucleus of maturing PDC following TLR9 activation, and that PDC express on the plasma membrane the bestcharacterized receptor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 66 publications
5
128
2
4
Order By: Relevance
“…12 A prominent DAMP that has been linked to immunogenic cell death is HMGB1, which activates DCs via TLR2/4 and RAGE receptors. [40][41][42][43][44] Interestingly, we found that RLH-activated tumor cells released high levels of HMGB1. However, we ruled out a significant contribution of HMGB1 or other endogenous TLR ligands to DC activation as DCs generated from mice deficient in specific TLR, TLR signaling pathways or RAGE showed unimpaired DC activation.…”
Section: Discussionmentioning
confidence: 78%
“…12 A prominent DAMP that has been linked to immunogenic cell death is HMGB1, which activates DCs via TLR2/4 and RAGE receptors. [40][41][42][43][44] Interestingly, we found that RLH-activated tumor cells released high levels of HMGB1. However, we ruled out a significant contribution of HMGB1 or other endogenous TLR ligands to DC activation as DCs generated from mice deficient in specific TLR, TLR signaling pathways or RAGE showed unimpaired DC activation.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, antagonists of HMGB1/RAGE/ TLRs might have therapeutic potential for the treatment of systemic septic diseases. [53] Anti-HMGB1 therapies of sepsis A growing body of studies have demonstrated that HMGB1, released passively by necrotic or damaged cells or actively by macrophages/monocytes, causes inflammatory responses and sepsis. [6,[10][11] Passive immunization with anti-HMGB1 antibodies signifi cantly protected against lethal endotoxemia in mice, even when treatment was delayed 2 hours after endotoxin exposure.…”
Section: Receptor(s) For Hmgb1 and Related Intracellular Signaling Inmentioning
confidence: 99%
“…As HMGB1 has been shown to be potent to stimulate myeloid and plasmacytoid DC maturation and cytokine secretion, 26,27 we hypothesized that HMGB1 may augment Th17 response by stimulating DC secretion of cytokines (eg, TGF-b and/or IL-6) relevant to Th17 development. To address this hypothesis, we established MLC assays by using BMDCs derived from donor mice and splenic T cells received from recipient mice.…”
Section: Hmgb1 Polarizes Th17 Response By Stimulating DC Secretion Ofmentioning
confidence: 99%